2020
DOI: 10.5194/nhess-2020-244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beachgoers’ ability to identify rip currents at a beach in situ

Abstract: Abstract. Rip currents (rips) are the leading cause of drowning on surf beaches worldwide. A major contributing factor is that many beachgoers are unable to identify rip currents. Previous research has attempted to quantify beachgoers' rip spotting ability using photographs of rip currents, without identifying whether this usefully translates into an ability to spot a rip current in situ at the beach. This study is the first to compare beachgoers ability to spot rip currents in photographs and in situ at a bea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 31 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…It should be acknowledged that the results of this surveybased study are subject to a variety of well-known response biases that are inherent in many types of questionnaires, such as agreement bias, prestige bias, and confirmation bias (Choi and Pak, 2005;Ménard et al, 2018;Davies, 2020). These types of bias also apply to previous studies involving surveys of beachgoer safety knowledge (Sherker et al, 2010;Williamson et al, 2012;Caldwell et al, 2013;Brannstrom et al, 2014;Fallon et al, 2018;Llopis et al, 2018;Locknick and Houser, 2021;Pitman et al, 2021). These studies were all conducted on beaches with lifeguards, with the exception of Sherker et al (2010), who did not discriminate results from respondents on patrolled and unpatrolled beaches.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…It should be acknowledged that the results of this surveybased study are subject to a variety of well-known response biases that are inherent in many types of questionnaires, such as agreement bias, prestige bias, and confirmation bias (Choi and Pak, 2005;Ménard et al, 2018;Davies, 2020). These types of bias also apply to previous studies involving surveys of beachgoer safety knowledge (Sherker et al, 2010;Williamson et al, 2012;Caldwell et al, 2013;Brannstrom et al, 2014;Fallon et al, 2018;Llopis et al, 2018;Locknick and Houser, 2021;Pitman et al, 2021). These studies were all conducted on beaches with lifeguards, with the exception of Sherker et al (2010), who did not discriminate results from respondents on patrolled and unpatrolled beaches.…”
Section: Discussionmentioning
confidence: 97%
“…6e) could be interpreted as a rip current, when in fact it was not. These limitations have previously been identified by Hatfield et al (2013), Ménard et al (2018), and Pitman et al (2021), who have all suggested that future rip identification skills should be assessed with the use of video.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations